VETERINARY AND SANITARY EVALUATION OF THE CHEMICAL COMPOSITION OF PORK OBTAINED FROM PIGS AFFECTED BY PORCINE REPRODUCTIVE AND RESPIRATORY SYNDROME AND PORCINE CIRCOVIRUS INFECTION - Zh. Sultanuly; M. Mambetaliev; A. Zhumageldiev; S. Przemyslaw (Animal Health and Biosafety, 2026)
The purpose of our study was to determine the vitamin content of pork meat from pigs infected with reproductive respiratory syndrome (RRS) and circovirus infection (PCV). The results of the study showed that the fat content in the meat of pigs in the control group (healthy) was higher than in the experimental group, and the level of vitamins (A, E, B1, B2, PP) in the meat of pigs in the experimental group was reduced. Protein is involved in physiological and biochemical phenomena, its effectiveness and nutritional value depend on the content of vitamins in it. The usefulness of protein in its composition is due to the presence of all the vitamins necessary for the body. In this regard, we comparatively studied the vitamin content of pork meat in the control group and in the experimental group. Vitamin E improves the function of muscles and gonads and participates in physiological processes in the body. Vitamins of group B (B1, B2) affect normal growth, biochemical reactions and rapid healing of wounds. Vitamin PP ensures biological oxidation processes in the body. According to the results of the research, the content of vitamins in the meat of healthy piglets is higher than in the meat of sick piglets, which is an important indicator of nutritional value, which is related to the health and productivity of the animal.